Indonesian Workers' Mental Health Protection: An Urgency? - Wiranto Mustamin; Budi Santoso; Syahrul Sajidin (Fakultas Hukum, Universitas Internasional Batam, 2022)
This study aims to determine the urgency of setting corporate responsibility norms for the protection of workers' mental health and to analyze the concept of regulating workers' mental health protection in Indonesia. This research is a normative legal research with a statue approach and a conceptual approach. The results obtained indicate that the protection of workers' mental health is urgent, there are at least 2 (two) reasons why this is urgent to be regulated, namely: First, the juridical reason that there is no specific regulation that regulates the protection of mental health of workers in Indonesia. Second, the sociological reason that mental health can burden families, communities, and governments. In addition, the mental health of workers can harm the national economy to the global economy and affect the bottom line of the business or the company's net profit through decreased productivity. The concept of regulating workers' mental health protection in Indonesia can be done by revising PERMENAKER Number 5 of 2018 concerning Occupational Safety and Health. In this case, the revision is intended to add work anxiety, job burnout, and depression into the standard of psychological factors.